Brackish groundwater membrane system design for sustainable irrigation: optimal configuration selection using analytic hierarchy process and multi-dimension scaling - Lew, Beni; Trachtengertz, Lolita; Ratsin, Shany; Oron, Gideon; Bick, Amos (Frontiers in Environmental Science, 2014)
The recent high demands for reuse of salty water for irrigation affected membrane producers to assess new potential technologies for undesirable physical, chemical and biological contaminants removal. This paper studies the assembly options by the analytic hierarchy process (AHP) model and the multi-dimension scaling (MDS) techniques. A specialized form of MDS (CoPlot software) enables presentation of the AHP outcomes in a two dimensional space and the optimal model can be visualized clearly. Four types of 8" membranes were selected: (i) Nanofiltration low rejection and high flux (ESNA1-LF-LD, 86% rejection, 10,500gpd); (ii) Nanofiltration medium rejection and medium flux (ESNA1-LF2-LD, 91% rejection, 8,200gpd); (iii) Reverse Osmosis high rejection and high flux (CPA5-MAX, 99.7 rejection, 12,000gpd) ; and (iv) Reverse Osmosis medium rejection and extreme high flux (ESPA4-MAX, 99.2 rejection, 13,200gpd). The results indicate that: (i) Nanofiltration membrane (High flux and Low rejection) can produce water for irrigation with valuable levels of nutrient ions and a reduction in the sodium absorption ratio (SAR), minimizing soil salinity; this is an attractive option for agricultural irrigation and is the optimal solution; and (ii) implementing the MDS approach with reference to the variables is consequently useful to characterize membrane system design.